2019
DOI: 10.1021/acs.inorgchem.9b00849
|View full text |Cite
|
Sign up to set email alerts
|

Molten Alkali Halide Flux Growth of an Extensive Family of Noncentrosymmetric Rare Earth Sulfides: Structure and Magnetic and Optical (SHG) Properties

Abstract: Twenty new alkali rare earth thiosilicates and thiogermanates with the general formula ALnTS4 (A = alkali metal, Ln = lanthanide, and T = Si, Ge) were grown as X-ray diffraction-quality single crystals from molten alkali chloride fluxes. These include KNdSiS4, KPrSiS4, RbLnSiS4 (Ln = Ce, Pr, Nd, Gd, Tb, Dy, and Ho), RbLaGeS4, CsLnSiS4 (Ln = La, Pr, and Nd), and CsLnGeS4 (La, Ce, Pr, Nd, Eu, Gd, and Tb). Herein, we discuss the use of a molten chloride flux growth approach for the preparation of the title compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…However, only the [GeO 2 Q 2 ] and [GeOS 3 ] units have been identified so far. The [GeOS 3 ] unit is found in Ae 2 MGe 2 S 6 O (Ae = Sr, Ba; M = Zn, Mn) compounds, which belong to the melilite-type sturcture. The [GeO 2 Q 2 ] units appear in the compounds of AeGeOQ 2 (Ae = Ba, Sr; Q = S, Se), which crystallize ina noncentrosymmetric (NCS) structure ( P 2 1 2 1 2 1 ). The [GeO 2 Q 2 ] tetrahedra connect to each other via corner sharing of O atoms, forming unique 1∞[GeQ 2 O] 2– helical chains.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the [GeO 2 Q 2 ] and [GeOS 3 ] units have been identified so far. The [GeOS 3 ] unit is found in Ae 2 MGe 2 S 6 O (Ae = Sr, Ba; M = Zn, Mn) compounds, which belong to the melilite-type sturcture. The [GeO 2 Q 2 ] units appear in the compounds of AeGeOQ 2 (Ae = Ba, Sr; Q = S, Se), which crystallize ina noncentrosymmetric (NCS) structure ( P 2 1 2 1 2 1 ). The [GeO 2 Q 2 ] tetrahedra connect to each other via corner sharing of O atoms, forming unique 1∞[GeQ 2 O] 2– helical chains.…”
Section: Introductionmentioning
confidence: 99%
“…Rare‐earth elements have unique fluorescent and magnetic properties, because they possess unique outer‐shell electronic structures enabling diverse charge transfer such as D→F, H→P, F→L, etc., and containing a number of unpaired f orbit electrons. Furthermore, they possess large atomic radii and usually exhibit diverse coordination modes; for example, the coordination number can vary from 6 to 14 in similar coordinating compounds, offering a wide stage for constructing all kinds of compounds .…”
Section: Introductionmentioning
confidence: 99%
“…For postreaction workup, methanol proved to be an effective solvent as it is sufficiently polar to dissolve the ionic alkali chloride fluxes and, at the same time, sufficiently water free to avoid degrading the product thiophosphate compounds . All compositions reported herein are stable for several days when stored in closed glass vials wrapped in Parafilm.…”
Section: Resultsmentioning
confidence: 96%
“…Klawitter et al reported on the first quaternary alkaline-earth rare earth thiophosphates, Ba 3 Ln 2 (PS 4 ) 4 (Ln = Gd – Er), utilizing BaCl 2 as the flux . For a long time, zur Loye and co-workers have utilized halide flux crystal growth approaches to prepare diverse complex oxides and recently demonstrated that alkali halide fluxes are extremely effective as the solvent for the crystallization of complex chalcogenides. The relative ease with which halide fluxes can be removed in postreaction workup and the fact that halide fluxes produce crystals of compounds in typically good yields and phase pure form make them an attractive flux.…”
Section: Introductionmentioning
confidence: 99%